DNA barcoding A tool for conservation biology - Devi, Bhanita; Bharti, P K (Indian Farming, 2018)
DNA barcoding is a useful molecular technique for the identification of unknown organisms at any life stage which will greatly facilitate and complement taxonomic studies. It can be used at any stage of life of an organism and on a wide range and will help in the identification and conservation of the evolutionary processes that generate and preserve biodiversity. This technology decreases the number of organisms that have to be collected in the field and reduces the amount of time between collection and identification. DNA barcoding can also be used as a starting place in the design of species specific primers that can be used for raw water and other environmental samples.